Thermal behavior of PLA and calcium phosphate compositions; AIP Conference Proceedings; Vol. 2310, iss. 1 : Physical Mesomechanics. Materials with Multilevel Hierarchical Structure and Intelligent Manufacturing Technology - Petrovskaya T. S. Tatyana Semyonovna (2020, 2020)
Title screen